2006
DOI: 10.1093/ecam/nem027
|View full text |Cite
|
Sign up to set email alerts
|

Aromatherapy Massage Affects Menopausal Symptoms in Korean Climacteric Women: A Pilot‐Controlled Clinical Trial

Abstract: This study investigated the effects of aromatherapy massage on menopausal symptoms in Korean climacteric women. Kupperman's menopausal index was used to compare an experimental group of 25 climacteric women with a wait-listed control group of 27 climacteric women. Aromatherapy was applied topically to subjects in the experimental group in the form of massage on the abdomen, back and arms using lavender, rose geranium, rose and jasmine in almond and primrose oils once a week for 8 weeks (eight times in total). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 10 publications
(13 reference statements)
1
37
0
3
Order By: Relevance
“…Geranium extract reduces menopausal symptoms and depression (25). Aroma therapy reduces climacteric symptoms such as hot flashes, depression and pain during intercourse (25,31). In a study by Malakoti et al on the effect of aromatherapy on sexual function of lactating women, improvement was observed in lactating women 40 days after the use of aroma (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geranium extract reduces menopausal symptoms and depression (25). Aroma therapy reduces climacteric symptoms such as hot flashes, depression and pain during intercourse (25,31). In a study by Malakoti et al on the effect of aromatherapy on sexual function of lactating women, improvement was observed in lactating women 40 days after the use of aroma (32).…”
Section: Discussionmentioning
confidence: 99%
“…The participants had used aromatherapy massage 30 minutes a week for 8 weeks (31). In a study by Marzouk et al on nursing students …”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of an earlier study that examined the effect of aromatherapy massage on women experiencing menopausal symptoms. 23 Another uncontrolled trial, which examined the impact of aromatherapy massage on menopausal symptoms, showed improvement of menopausal symptoms through aromatherapy massage. 24 As the results of our study showed, massage therapy also has positive effects because of the lower score averages reported by the placebo massage group after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, to our knowledge, there are few studies related to menopause. Despite the results of some studies 23,24 that show the potential usefulness of aromatherapy in treating menopause, scientific research on the subject is limited. We have been unable to find any previously published studies of the effect of aromatherapy on menopausal symptoms in Iran.…”
mentioning
confidence: 99%
“…[1][2][3] Beyond these sensory and psychological benefits, the topical use of some plant-derived chemicals has been shown to cause smooth muscle relaxation. [4][5][6][7] The long-chained plantderived carbon based chemicals 1,8-cineole ( Figure 1a) and α-pinene ( Figure 1b) and the short-chained plant-derived carbon based chemicals cis-3-hexen-1-ol ( Figure 1c) and trans-2-hexenal ( Figure 1d) may also have smooth muscle relaxing properties. Mechanisms by which organic chemicals may induce smooth muscle relaxation include impeding the propagation of NTIs, reducing EJCs or uncoupling the syncytium of smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%